A Protocol for Isolation and Enriched Monolayer Cultivation of Neural Precursor Cells from Mouse Dentate Gyrus - Babu, Harish; Claasen, Jan-Hendrik; Kannan, Suresh; Rünker, Annette E.; Palmer, Theo; Kempermann, Gerd (Frontiers in Neuroscience, 2011)
In vitro assays are valuable tools to study the characteristics of adult neural precursor cells under controlled conditions with a defined set of parameters. We here present a detailed protocol based on our previous original publication (Babu et al., Enriched monolayer precursor cell cultures from micro-dissected adult mouse dentate gyrus yield functional granule cell-like neurons, PLoS One 2007, 2:e388) to isolate neural precursor cells from the hippocampus of adult mice and maintain and propagate them as adherent monolayer cultures. The strategy is based on the use of Percoll density gradient centrifugation to enrich precursor cells from the micro-dissected dentate gyrus. Based on the expression of Nestin and Sox2, a culture-purity of more than 98% can be achieved. The cultures are expanded under serum-free conditions in Neurobasal A medium with addition of the mitogens EGF and FGF2 as well as the supplements Glutamax-1 and B27. Under differentiation conditions, the precursor cells reliably generate approximately 30% neurons with appropriate morphological, molecular and electrophysiological characteristics that might reflect granule cell properties as their in vivo counterpart. We also highlight potential modifications to the protocol.